Unstructured data analytics : how to improve customer acquisition, customer retention, and fraud detection and prevention /: how to improve customer acquisition, customer retention, and fraud detection and prevention. (2017) - Isson, Jean Paul, 1971-; Hwang, Minha
No abstract available